SPORTS FEAT AS AN EXPRESSION OF PATRIOTIC DUTY AND MORAL EXCELLENCE - Madaminov Bakhodir Sharifjonovich (Web of Journals Publishing, 2025)
This article examines the phenomenon of an outstanding athlete in a philosophical context as the embodiment of patriotism, moral idealism, and spiritual self-improvement of an individual. Special attention is given to the role of heroic figures in sports who, as symbols of national pride, contribute to strengthening the moral foundations of society and shaping the values of youth.
Keywords: Philosophy of sport, physical culture, patriotism, moral ideal, heroism, spiritual self-improvement, humanism, personality, ideal, Shavkat Mirziyoyev, youth of Uzbekistan, moral values.